Borrowing Stigma and Lender of Last Resort Policies - Hu, Yunzhi; Zhang, Hanzhe (Journal of Financial and Quantitative Analysis, 2025)
How should the lender of last resort provide liquidity to banks during periods of financial distress? During the 2008–2010 crisis, banks avoided borrowing from the Fed’s long-standing discount window but actively participated in its special monetary program, the Term Auction Facility, although both programs had the same borrowing requirements. Using an adverse selection model with endogenous borrowing decisions, we explain why the two programs suffer from different stigma costs and how the introduction of TAF incentivized banks’ borrowing. We discuss the empirical relevance of the model’s predictions. [Banks] deliberately did not ask for the liquidity they needed for fear of damaging their reputation—the ‘stigma’ problem… I do not think we were conscious of this before the crisis started and I do not think central banks have a convincing answer to it… This is, I think, still a challenge in how to manage the process of central bank provision of liquidity support. This is one of the big intellectual issues that has not been fully resolved. (Governor Mervyn King, Bank of England (2016)) For various reasons, including the competitive format of the auctions, [Term Auction Facility] has not suffered the stigma of conventional discount window lending and has proved effective for injecting liquidity into the financial system… Another possible reason that [Term Auction Facility] has not suffered from stigma is that auctions are not settled for several days, which signals to the market that auction participants do not face an immediate shortage of funds. (Ben Bernanke, testimony to U.S. House of Representatives (2010))